Inhalable nanotherapeutics to improve treatment efficacy for common lung diseases. (10th October 2019) - Anderson, Caleb F.; Grimmett, Maria E.; Domalewski, Christopher J.; Cui, Honggang
Abstract: Respiratory illnesses are prevalent around the world, and inhalation‐based therapies provide an attractive, noninvasive means of directly delivering therapeutic agents to their site of action to improve treatment efficacy and limit adverse systemic side effects. Recent trends in medicine and nanoscience have prompted the development of inhalable nanomedicines to further enhance effectiveness, patient compliance, and quality of life for people suffering from lung cancer, chronic pulmonary diseases, and tuberculosis. Herein, we discuss recent advancements in the development of inhalable nanomaterial‐based drug delivery systems and analyze several representative systems to illustrate their key design principles that can translate to improved therapeutic efficacy for prevalent respiratory diseases. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Respiratory Disease Abstract : Many nanomaterials can be used to develop inhalable nanomedicines that can be administered with various aerosolization devices. Pulmonary delivery of these systems leads to enhanced therapeutic efficacy and safety by targeting diseased cells in many common lung diseases, such as lung cancer, chronic obstructive pulmonary disease (COPD), asthma, and tuberculosis.